2012
DOI: 10.2105/ajph.2012.300699
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Substance Use and Other Illegal Behaviors and Racial Disparities in Criminal Justice System Involvement: Findings From a US National Survey

Abstract: We used data from a national survey to examine arrest rate disparities between African American and White adolescents (aged 12-17 years; n=6725) in relation to drug-related and other illegal behaviors. African American adolescents were less likely than Whites to have engaged in drug use or drug selling, but were more likely to have been arrested. Racial disparities in adolescent arrest appear to result from differential treatment of minority youths and to have long-term negative effects on the lives of affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 14 publications
2
34
0
Order By: Relevance
“…Consistent with previous research (Johnston et al, 2013; Kakade et al, 2012; Wu et al, 2011), we also found that while Black youths engaged in less problematic substance use than their non-Black peers, they remain overrepresented in incarcerated populations. In fact, being a Black adolescent was associated with less polysubstance use as compared to being a White adolescent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous research (Johnston et al, 2013; Kakade et al, 2012; Wu et al, 2011), we also found that while Black youths engaged in less problematic substance use than their non-Black peers, they remain overrepresented in incarcerated populations. In fact, being a Black adolescent was associated with less polysubstance use as compared to being a White adolescent.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, compared to White youth, Black youth have a lower likelihood of substance use and are less likely to meet criteria for substance use disorders, while Latino youth report the highest levels of drug use (Johnston et al, 2013; Wu, Woody, Yang, Pan & Blazer, 2011). While Black youth are less likely than White youth to have engaged in substance use, a representative national survey of approximately 7,000 adolescents demonstrated that Blacks are more likely to be arrested for drug-related and other delinquent behaviors (Kakade et al, 2012). This discrepancy in incarceration rates for Black youth may suggest inherent bias in juvenile justice policies (Weich & Angulo, 2000) and/or disproportionate levels of engagement in risky drug-related behaviors (i.e., involvement with drug dealing; Centers & Weist, 1998) among Black youth as compared to White youth.…”
Section: Risk Factors For Polysubstance Usementioning
confidence: 99%
“…MCLS connectivity and its relationship with SUD has never been examined in a minority population. Given that the determinants (Clark et al, 2015 ) and consequences (Kakade et al, 2012 ) of SUD may differ depending on one’s racial/ethnic and socio-cultural background, the neural underpinnings of SUD could arguably differ across racial/ethnic groups. For example, processes underlying reinforcement learning and substance use may differ when the use of illegal substances can have dramatic consequences (e.g., arrest), as is more common among minorities relative to White youth (Kakade et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given that the determinants (Clark et al, 2015 ) and consequences (Kakade et al, 2012 ) of SUD may differ depending on one’s racial/ethnic and socio-cultural background, the neural underpinnings of SUD could arguably differ across racial/ethnic groups. For example, processes underlying reinforcement learning and substance use may differ when the use of illegal substances can have dramatic consequences (e.g., arrest), as is more common among minorities relative to White youth (Kakade et al, 2012 ). Puerto Ricans, the second largest Latino subgroup in the US, have the highest rates of SUD among all US Latino subgroups (Alegria et al, 2006 , 2007 ; Caetano et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there remains a need to identify factors that are associated with or indicate risk for marijuana use among those at greatest risk for suffering these adverse outcomes (i.e., African Americans) (Des Jarlais, McCarty, Vega, & Bramson, 2013;Green et al, 2010;Kakade et al, 2012;Zapolski, Pedersen, McCarthy, & Smith, 2014).…”
Section: Introductionmentioning
confidence: 99%